Reduced Content of Lysyl-Phosphatidylglycerol in the Cytoplasmic Membrane Affects Susceptibility to Moenomycin, as Well as Vancomycin, Gentamicin, and Antimicrobial Peptides, in Staphylococcus aureus - Nishi, Hiromi (American Society for Microbiology, 2004)
An association between moenomycin resistance and vancomycin intermediate resistance in Staphylococcus aureus was demonstrated previously. Thus, to elucidate the mechanism of vancomycin intermediate resistance, we searched for factors contributing to moenomycin resistance. Random Tn551 insertional mutagenesis of methicillin-resistant S. aureus strain COL yielded three mutants with decreased susceptibilities to moenomycin. Correspondingly, these mutants also exhibited slightly decreased susceptibilities to vancomycin. Genetic analysis revealed that two of the mutants had Tn551 insertions in the fmtC (mprF) gene, which is associated with the synthesis of lysyl-phosphatidylglycerol. The third Tn551 insertion was located in the lysC gene, which is involved in the biosynthesis of lysine from aspartic acid. Consequently, mutations in both of these loci reduced the lysyl-phosphatidylglycerol content in the cell membrane, giving it a more negative net charge. The positively charged antibiotic gentamicin and cationic antimicrobial peptides such as β-defensins and CAP18 were more effective against the mutants. The levels of moenomycin and vancomycin binding to intact cells was also greater in the mutants than in the wild type, while the binding affinity was not altered when cells boiled in sodium dodecyl sulfate were used, indicating that both agents had higher affinities for the negatively charged membranes of the mutants. Therefore, the membrane charge of S. aureus appears to influence the efficacies of moenomycin, vancomycin, and other cationic antimicrobial agents.